2005
DOI: 10.1111/j.1537-2995.2005.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell loss and recovery in umbilical cord blood processing: a comparison of postthaw and postwash samples

Abstract: Our data indicate that the thawing and washing results in a substantial loss of cells, with TNC loss approaching 20 percent when compared with PF counts; the wash step was responsible for nearly half of the cell loss. The reduced PT viability was expected. Elapse of time PW resulted in further loss of NCs but no detectable significant changes in CD34+ cell content and viability and/or CFU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 30 publications
9
87
2
3
Order By: Relevance
“…These observations suggest the CB unit selection criteria should include CD34 þ cell counts despite the variability induced by multiple techniques used for cell numeration in CB banks. In contrast to previously published studies, 26,27 we observed a significant correlation prefreeze/post-thaw by the use of a single cytometry platform for the quality control step. As suggested in preliminary studies about CD34 þ cell measurement 19,20 and CB thawing, 28 our results confirm, under transplantation conditions, that standardization of CD34 þ cell numeration techniques and use of single platform cytometry are necessary to better estimate the CD34 þ cell influence in CB transplantation.…”
Section: Discussioncontrasting
confidence: 99%
“…These observations suggest the CB unit selection criteria should include CD34 þ cell counts despite the variability induced by multiple techniques used for cell numeration in CB banks. In contrast to previously published studies, 26,27 we observed a significant correlation prefreeze/post-thaw by the use of a single cytometry platform for the quality control step. As suggested in preliminary studies about CD34 þ cell measurement 19,20 and CB thawing, 28 our results confirm, under transplantation conditions, that standardization of CD34 þ cell numeration techniques and use of single platform cytometry are necessary to better estimate the CD34 þ cell influence in CB transplantation.…”
Section: Discussioncontrasting
confidence: 99%
“…In most studies, CD34 + cell selection is done before initiating cell culture [46], but the CD34 + cell selection itself is associated with a substantial loss of progenitor cells. This cell loss, which may not be significant for smaller children, may become critical in reaching a suitable dose for transplant in older children and adults [47].…”
Section: Ex Vivo Expansion Of Hscmentioning
confidence: 99%
“…Laroche et al [47] stated that thawing and washing result in loss of cells approaching 20% when compared with pre-freeze counts, with the wash step responsible for nearly half of this cell loss. However, Beshlawy et al [48], using umbilical cord blood derived hematopoietic stem cells, detected mean fold expansion of 6.64 ± 3.34 with stem cell factor alone, 7.38 ± 2.86 with both stem cell factor and IL-3, and 8.11 ± 4.49 with IL-3 alone after 2 days culture of the samples frozen for 2 weeks.…”
Section: Ex Vivo Expansion Of Hscmentioning
confidence: 99%
“…Limitations to UCB transplantation (UCBT) for adult patients have been identified, including delayed engraftment due to the low dose of infused stem cells. 1 Unnecessary cell loss during processing, estimated to be around 20% using washing techniques, 2 can further reduce the infused stem cell dose. Larger umbilical cord grafts have been shown to improve time to engraftment and decrease transplant-related mortality.…”
Section: Introductionmentioning
confidence: 99%